Papillary carcinoma of the thyroglossal duct cyst: case report. - Nasrollah Maleki; Manouchehr Iranparvar Alamdari; Iraj Feizi; Zahra Tavosi (Tehran University of Medical Sciences, 2014)
Thyroglossal duct cysts are the most common form of congenital cysts on the neck. The incidence of thyroid papillary carcinoma in thyroglossal duct cyst is less than 1%. In most cases the diagnosis is made postoperatively. We present a 22-year-old female with thyroid papillary carcinoma arising from thyroglossal duct cyst,identified in pathologic study after sistrunk operation.In our case there was neither invasion to adjacent tissue nor lymph node involvement.The patient then underwent total thyroidectomy and bilateral neck dissection. The patient was treated with radioactive iodide and thyroid suppression therapy was given as adjuvant treatment.The patient has been following for two years without any metastasis.